The use of laboratories as a pedagogical intervention of the PIBID of Biological Sciences of the State University of Alagoas-UNEAL / O uso de laboratórios como uma intervenção pedagógica do PIBID de Ciências Biológicas da Universidade Estadual de Alagoas-UNEAL - Fernanda Stefanny Lima Sobrinho; Mayara Camila Santos Silva; Viviane Patrícia Pereira Félix; Josefa Betânia Vilela Costa (Universidade Estadual de Alagoas, 2018)
This article is based on the perception that the development of laboratory classes facilitates the process of teaching and learning. Therefore, providing the evolution of the students, allowing them to inquire and reflect on certain matters and form a new vision on the same theme. The purpose is work the overruns of student learning, proposing intervention activities such as the use of practical classes in science and computer labs, involving technological resources as used by the society actual. Dynamic activities were carried out in both laboratories in the State School Professor Antonia Izaura Lisbon (EPIAL), located in the city of Arapiraca-Al, with the first and second year high school students. This work was developed with the help of subproject grantees "Innovative Teaching Practices Biology with Science and Technology Support", the State University of Alagoas-UNEAL. The data collected are presented by means of questionnaires administered to students participants of interventions. There is a clear need for training and further training of teachers in the use of practical classes, it is necessary that teachers are trained to assume the role of facilitator of knowledge building and not a mere transmitter of information. The results allow to identify the importance and contribution that these classes bring. Hereupon, it is considered of utmost importance the development of practical classes in schools because, through these, you can develop a sense-critical student, turning it more participatory